Nitric oxide suppresses NLRP3 inflammasome activation and protects against LPS-induced septic shock - Mao, Kairui (Nature Publishing Group, 2013)
Inflammasomes are multi-protein complexes that trigger the activation of caspase-1 and the maturation of interleukin-1β (IL-1β), yet the regulation of these complexes remains poorly characterized. Here we show that nitric oxide (NO) inhibited the NLRP3-mediated ASC pyroptosome formation, caspase-1 activation and IL-1β secretion in myeloid cells from both mice and humans. Meanwhile, endogenous NO derived from iNOS (inducible form of NO synthase) also negatively regulated NLRP3 inflammasome activation. Depletion of iNOS resulted in increased accumulation of dysfunctional mitochondria in response to LPS and ATP, which was responsible for the increased IL-1β production and caspase-1 activation. iNOS deficiency or pharmacological inhibition of NO production enhanced NLRP3-dependent cytokine production in vivo, thus increasing mortality from LPS-induced sepsis in mice, which was prevented by NLRP3 deficiency. Our results thus identify NO as a critical negative regulator of the NLRP3 inflammasome via the stabilization of mitochondria. This study has important implications for the design of new strategies to control NLRP3-related diseases.